Bite by moray eel - Barreiros, J. P.; Haddad, V. [UNESP] (FapUNIFESP (SciELO), 2008)
Injuries caused by moray eels are not a common problem, but are distributed throughout the globe, affecting mainly fishermen while manipulating hooked or netted fish. On a lesser scale, scuba divers and snorkelers, practicing or not spear fishing, are occasional victims of bites. With more than 185 species distributed among 15 genera, mostly in tropical to temperate shallow water, moray eels easily come into contact with humans and occasional injuries are not uncommon. The current study reports one case of moray eel bite and discusses the circumstances in which the accident happened, as well as wound evolution and therapy.
Keywords: Bites in humans; Dangerous marine fish; Moray eels